Preparation and characterization of natural silk fiber-reinforced polypropylene and synthetic E-glass fiber-reinforced polypropylene composites: a comparative study - Alam, A. K. M. M.; Shubhra, Quazi T.H.; Al-Imran, Gazi; Barai, Sanjoy; Islam, Mir Sujaul; Rahman, M. Mahbubur (SAGE Publications, 2011)
Bombyx mori silk fiber-reinforced polypropylene (PP) matrix and E-glass fiber-reinforced PP matrix composites were fabricated using compression molding. The prepared silk/PP composite tensile strength (TS), bending strength (BS), and impact strength (IS) were 55.1 MPa, 56.3 MPa, and 17 kJ/m2, respectively. E-glass fiber-reinforced PP matrix composites were fabricated in the same way and TS, BS, and IS values of these composites were 128.7 MPa, 141.6 MPa, and 19 kJ/m2, respectively. Environmental degradation of the composites showed that silk/PP composites degrade faster. Other degradation studies like thermal aging and soil degradation tests also gave similar result.